Possible half-metallicity and variable range hopping transport in Sb-substituted Fe2TiSn Heusler alloys - Chaudhuri, S; Bhobe, P A; Nigam, A K (Journal of physics. Condensed matter, 2018)
The investigation of the magnetotransport properties on Fe2TiSn1−xSbx with 0 ⩽x⩽ 0.6 are presented in this paper. The substitution of Sb in place of Sn decreases the anti-site disorder as evident from x-ray diffraction patterns as well as from transport properties measurement. The much-disputed upturn in low temperature electrical resistivity of Fe2TiSn has been demonstrated to be a result of weak localization induced by anti-site disorder. With increased Sb substitution ( 25%) the metallic transport behavior of Fe2TiSn changes to semiconductor-like. At low temperature, carrier transport in such compositions occurs via the variable range hopping mechanism. Moreover, a systematic increase in the anomalous Hall voltage is observed with increasing Sb-content, attributable to a side jump or Berry phase curvature effect. Electrical resistivity in the entire temperature regime hints towards half metallicity of the system. Our ab initio electronic structure calculations using generalised gradient approximation formalism further supports the results of our magnetotransport study.